In Search of Legitimacy in Post-revolutionary China: Bringing Ideology and Governance Back In - Heike Holbig; Bruce Gilley (German Institute of Global and Area Studies (GIGA), 2010)
The contemporary politics of China reflect an ongoing effort by the ruling Chinese Communist Party (CCP) to claim the right to rule in light of the consequences of economic development, international pressures, and historical change. China stands out within the Asian region for the success the regime has achieved in this effort. By focusing on the changes in China's elite discourse during the reform period and particularly during the last decade, this paper aims to elaborate on the relative importance of various sources of legitimacy as they shift over time, as well as on their inherent dilemmas and limitations. There is evidence of an agile, responsive, and creative party effort to relegitimate the postrevolutionary regime through economic performance, nationalism, ideology, culture, governance, and democracy. At the same time, the paper identifies a clear shift in emphasis from an earlier economic-nationalistic approach to a more ideological-institutional approach. – – Die Versuche der Kommunistischen Partei Chinas (KPCh), vor dem Hintergrund wirtschaftlicher Entwicklung, internationalen Drucks und historischer Veränderungen die Legitimität ihrer Herrschaft zu wahren, prägen die gegenwärtige Politik Chinas. Innerhalb der asiatischen Region kann China dabei als vergleichsweise erfolgreich gelten. Ziel dieses Beitrags ist es, mit Blick auf Änderungen im innerchinesischen Elitediskurs während der Reformperiode und vor allem während des zurückliegenden Jahrzehnts, zu untersuchen, auf welche Legitimitätsquellen zurückgegriffen wird, wie ihre relative Bedeutung sich im Zeitverlauf verändert, und welche inhärenten Dilemmata und Beschränkungen damit verbunden sind. Identifiziert werden wirtschaftliche Performanz, Nationalismus, Ideologie, Kultur, Governance und Demokratie als die wichtigsten Quellen zur Relegitimierung eines durchaus agilen, responsiven und kreativen postrevolutionären Parteiregimes. Zugleich wird gezeigt, dass dabei eine klare Akzentverschiebung stattgefunden hat, und zwar von einem früheren Ansatz, der sich primär auf Wirtschaftswachstum und Nationalismus stützte, hin zu einem Ansatz, der Aspekte des ideologischen und institutionellen Wandels betont.
Keywords: 300; regime legitimacy; China; Chinese Communist Party; performance; nationalism; ideology; culturalism; governance; democracy